Current Concepts in Surgery for Wilms Tumor—The Risk and Function-Adapted Strategy - Godzinski, Jan; Graf, Norbert; Audry, Georges (European Journal of Pediatric Surgery, 2014)
This article describes the current status of surgical approach to Wilms tumor. Combined multimodal treatment including classical open nephrectomy is still the most recommended and offers excellent survivals. Patients suffering from Wilms tumor as potentially very long-term survivors also need great care of quality of their further life. Nephron-sparing surgery seems an important step in this regard; however, selection of patients is necessary to avoid failures and decreasing survival rate. A new method of describing this kind of procedure developed within the SIOP Renal Tumours Study Group (RTSG) offers an opportunity for further comparisons and assessment. Minimally invasive nephrectomy is not recommended in the treatment of Wilms tumor; however, in experienced hands and correctly selected (rare) cases, minimally invasive nephrectomy may offer the same outcome as the classical open approach. Lymph nodes sampling, essential for reliable staging, appeared rarely correct in children operated by this technique. Any competition with partial nephrectomy should be avoided in favor of the nephron-sparing approach. A small proportion of patients still create surgical difficulties and this is in fact the target group for further surgical reviews. Their prognosis seems at least in part surgeon-dependent. Few clinical factors available preoperatively (tumor side, age, and tumor volume) were detected as influencing potential risk of surgical failures. Once identified, this needs increased attention from the surgical point of view.
Keywords: Nephroblastoma; Surgery; SIOP; nephron sparing